2012
DOI: 10.1603/ec12236
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility and Selectivity of <I>Cnaphalocrocis medinalis</I> (Lepidoptera: Pyralidae) to Different Cry Toxins

Abstract: Effectiveness of four Cry toxins (Cry1Ac, Cry1Aa, Cry1Ab, and Cry1C) on Cnaphalocrocis medinalis (Guenée) (Lepidoptera: Pyralidae), collected from paddy fields in Jiaxing, Zhejiang Province, China, was evaluated in the laboratory. Bioassays showed that C. medinalis had different susceptibilities against four Cry toxins. The LC50 values of Cry1Ac, Cry1Ab, Cry1Aa, and Cry1C against C. medinalis were 0.405, 1.111, 1.939, and 1.246 microg/ml, respectively. Furthermore, the mortality of C. medinalis against differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…; Yang et al . ). However, there are only few reports on the toxicity of Cry1Da despite the fact that it is active against the polyphagous Spodoptera insects.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Yang et al . ). However, there are only few reports on the toxicity of Cry1Da despite the fact that it is active against the polyphagous Spodoptera insects.…”
Section: Introductionmentioning
confidence: 97%
“…There are many reports on testing different Cry toxins such as Cry1Aa, Cry1Ab and Cry1C against many insect larvae (Xue et al 2005;Yang et al 2012). However, there are only few reports on the toxicity of Cry1Da despite the fact that it is active against the polyphagous Spodoptera insects.…”
Section: Introductionmentioning
confidence: 99%
“…Environment-friendly methods are recommended in the pest control. Bacillus thuringiensis , as one of the important biological agents has been applied in the pest control for more than 60 years due to its crystal protein with insecticidal activity against insect pests [ 7 – 9 ]. Cry genes derived from B .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, transgenic broccoli containing both Cry1Ac and Cry1C Bt genes effectively controlled diamondback moths resistant to either single protein (Cao et al, 2002). Cry1Ig is a newly discovered gene which showed high insecticidal activity to lepidopterans (data unpublished), while Cry1Ac is an elite insecticidal Bt gene which was highly insecticidal to striped stem borer and rice leaf roller (Yang et al, 2012), two major rice pests in China. Furthermore, Ruiz de Escudero et al (2006) demonstrated that Cry1I shared different binding sites in midgut membrane vesicles from Cry1Ac, suggesting that cross resistance between Cry1Ac and Cry1Ig was unlikely to occur.…”
Section: Discussionmentioning
confidence: 99%